Correlation between severe infection and breast cancer metastases in the EORTC 10994/BIG 1-00 trial: Investigating innate immunity as a tumour suppressor in breast cancer. (February 2017) - Touati, Nathan; Tryfonidis, Konstantinos; Caramia, Franco; Bonnefoi, Hervé; Cameron, David; Slaets, Leen; Parker, Belinda S.; Loi, Sherene
Abstract: Background: Breast cancer cells which express an innate immune signature regulated by interferon regulatory factor 7 ( IRF7 ) have reduced metastatic potential. Infections can induce interferon signalling and may activate an anti-tumour immune response. We investigated whether 'severe infection' can be a clinical surrogate of this phenomenon and/or the presence of high levels of the IRF7 signature at diagnosis before neo-adjuvant chemotherapy (NACT) is associated with a reduced distant relapse risk, specifically in bones. Methods: Clinical data of the European Organisation for Research and Treatment of Cancer 10994/BIG 1-00 phase III trial which randomised 1856 patients treated with NACT between 2001 and 2006, were used. Severe infection was febrile neutropenia or any other grade III–IV infective adverse event during NACT. The IRF7 signature was calculated from gene expression data available for 160 patients on a pre-NACT biopsy. Cox models for distant relapse-free interval (DRFI) investigated the effect of the severe infection and IRF7 . Fine and Gray models studied the occurrence of bone metastases as first distant relapse. Results: Median follow-up was 4.8 years. No association between severe infection and DFRI was observed in the entire population (n = 1615 eligible patients) hazard ratio [(HR] = 0.99, 90% CI, confidence interval [CI] = 0.81–1.20). For IRF7 (N = 160), a trend towards an association with DRFI was observed (HR = 0.89 for a 50 unit increase, 90% CI = 0.78–1.02, p = 0.081). Higher levels of the IRF7 signature were significantly associated with a decreased bone metastases risk: (HR = 0.76 for a 50 unit increase, 95% CI, 0.62–0.94, p = 0.012). Conclusions: In this study it was shown that severe infection during NACT was not associated with decreased DRFI while high expression of the IRF7 gene signature was significantly associated with reduced bone relapse. This result may be useful for future adjuvant bisphosphonate/denosumab use. Highlights: Innate immunity has shown to prevent metastatic potential in pre-clinical models. Infection can activate an innate immune response regulated by interferon regulatory factor 7 (IRF7). Clinical data of the European Organisation for Research and Treatment of Cancer 10994/BIG 1-00 phase III trial were analysed to evaluate this hypothesis. High expression of the IRF7 gene signature was significantly associated with reduced bone relapse. The efficacy of adjuvant bisphosphonate/denosumab could be influenced by tumour IRF7 status.